Politik Identitas dalam Ruang Demokrasi Indonesia: Dinamika, Strategi, dan Implikasinya Terhadap Kohesi Sosial - Tumanggor, Timur; Azhar, Anang Anas (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
This study examines the construction and mobilization of identity politics in Indonesia's democratic space and its implications for social cohesion and the quality of democracy. Using a qualitative approach with a case study method, this study found that identity politics in Indonesia is consciously utilized by various political actors through symbols, religious and cultural narratives, and social media. Identity politics has been proven to form affectation-based political loyalty, but it has an impact on the exclusion, polarization, and delegitimization of democratic institutions. Phenomena such as the 2017 Jakarta Regional Elections and the 2019 General Election are concrete examples of how identity is used as an effective electoral strategy, but risks deepening social tensions. Nevertheless, identity politics also has constructive potential if it is managed within the framework of inclusive local culture and supported by Islamic communication principles such as tasamuh (tolerance), shura (deliberation), and ukhuwah (brotherhood). These values are able to form a harmonious space for dialogue and encourage fair political participation. This study recommends the need to strengthen multicultural education, public policies that support social integration, and the mainstreaming of cross-identity communication ethics as the foundation of a sustainable, inclusive, and upholding democracy that upholds Bhinneka Tunggal Ika.